Can International Practicum Foster Intercultural Competence Among Student Teachers? - Gerd Wikan; Jørgen Klein (European Teacher Education Network, 2017)
International practicum is potentially effective in preparing student teachers for work in a diverse classroom. The cultural shock they experience may catalyse a change in frames of reference, which in turn could lead to increased cultural sensitivity. However, this will depend on the ability of the student to reflect and elaborate on an existing point of view and habit of mind and transform them into a new frame of reference. The aim of this study is to investigate how the students' intercultural competence develops during a three-month practicum placement in Namibia. We present findings from a study of Norwegian student teachers before, during and after their international practicum. The main findings indicate that the international experience alone does not necessarily result in intercultural competence. In order to reach that goal emphasis should be put on student self-reflection in the preparation, implementation and debriefing of the program.